Epidemic of hate : violations of the human rights of gay men, lesbians, and transvestites in Brazil - Mott, Luiz Roberto (Bahia [Brazil] : International Gay and Lesbian Human Rights Commission, 1996)
Fonds Suzan Daniel (FSD)
Engels
Brochure